ARI IN CHILDREN: A CASE MANAGEMENT INTERVENTION IN ABBOTTABAD - Khan, Jahangir A; Addiss, David G (Journal of Ayub Medical College Abbottabad, 1996)
A community-based program of acute lower respiratory infection (ALRI) case management was conducted in a rural district of northern Pakistan. The impact on infant and child mortality of this program was evaluated. During 1985-1986, ALRI-specific mortality among children <5 years old living in 31 intervention villages was 6.3 deaths per 1 ( X X ) children per year compared with 14.4 in seven control villages (p=0.0001). Within one year after interventions were extended to the control villages in 1987, ALRI-specific mortality in these villages dropped by 55% to 6.5 per I ( X X ) children per year (p=0.06). Total child mortality in 1985-86 was 29.0 per 1000 children per year in the intervention villages and 39.4 in the control villages, a difference of 287c ft=0.01). With interventions in 1987, total child mortality in the control villages declined by 297c to 27.8 per 1000 children per year (p=0.09).